2022
DOI: 10.3389/fpubh.2022.926812
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic characteristics and transmission risk prediction of brucellosis in Xi'an city, Northwest China

Abstract: Human brucellosis (HB) has re-emerged in China since the mid-1990s, and exhibited an apparent geographic expansion shifted from the traditional livestock regions to the inland areas of China. It is often neglected in non-traditional epidemic areas, posing a serious threat to public health in big cities. We carried out a retrospective epidemiological study in Xi'an, the largest city in northwestern China. It utilizes long-term surveillance data on HB during 2008–2021 and investigation data during 2014–2021. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Therefore, it is significant to enhance the quarantine of livestock, strengthen the controls on livestock products to prevent contaminated products from entering the market [39] and strengthen the sterilization of animal products in food processing. Human brucellosis incidence was positively correlated with gross pastoral product in the middle reaches of the Yangtze River, which was consistent with the findings of Zhao et al [40]. The improvement of residential standards has accelerated the development of animal husbandry and the processing and transportation of livestock products, increasing the exposure of animal hosts [39].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, it is significant to enhance the quarantine of livestock, strengthen the controls on livestock products to prevent contaminated products from entering the market [39] and strengthen the sterilization of animal products in food processing. Human brucellosis incidence was positively correlated with gross pastoral product in the middle reaches of the Yangtze River, which was consistent with the findings of Zhao et al [40]. The improvement of residential standards has accelerated the development of animal husbandry and the processing and transportation of livestock products, increasing the exposure of animal hosts [39].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the average level of annual incidence of HB was observed to be 5.52 per 100,000 individuals in Shenyang, Liaoning Province, which was higher than that in China [ [16] , [17] , [18] , [19] , [20] ] and in Xian, Shanxi Province [ 35 ], but lower than that in Shanxi Province [ 36 , 37 ], the Inner Mongolia Autonomous Region [ 38 , 39 ], and Liaoning Province [ 24 , 25 ]. Shenyang, the capital city of Liaoning Province and Xian, the capital city of Shanxi Province, exhibit a higher degree of urbanization compared to other cities in their respective provinces.…”
Section: Discussionmentioning
confidence: 73%
“…Increased GDP can lead to higher investment in infrastructure, which is instrumental in improving the living standards of residents and enhancing the accessibility of medical resources. On the other hand, as the standard of living in China has improved, there has been an increased demand for animal protein, leading to a rise in livestock production, slaughter, and transportation for meat consumption 22 . Consequently, more individuals contact animal hosts and their vectors, potentially increasing the risk of disease transmission to humans 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increase in residents’ education funds has led to improvements in education levels and heightened disease awareness. As individuals become more educated, they are more likely to be aware of diseases and take necessary precautions 22 . Increased investment in education can enable a wider range of individuals to acquire an education, leading to a higher level of health and disease awareness among the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation